Propellants of University-Industry-Government synergy: Comparative study of Czech and Slovak manufacturing industries - Prokop, Viktor; Odei, Samuel Amponsah; Stejskal, Jan (My University, 2018)
The triple helix collaboration among universities, industries and governments resulting in the efficient creation of innovation has gained lofty scholarly attention in recent times. This institutional interdependence creates win-win outcomes leading to improved firms competitiveness, human capital development and general economic development. The rapid implementation of knowledge and outcomes of academic research emanating from universities and other public research organizations are crucial for firm’s competitiveness so firms are increasingly getting closer to the sources of knowledge and innovation. We examined the factors that influence firm’s cooperation with universities and government research entities in the Czech Republic and Slovakia by using data from the 2010–2012 Community Innovation Survey and the logistic regression models. The results of our analysis have demonstrated that both Czech and Slovak firms perceive their cooperation with universities as essential and beneficial for their innovative performance. Additionally, Slovak and Czech firms are self-sufficient and can provide basic input factors and capital goods necessary for their production hence they do not cooperate in this regard.
Synergie spolupráce univerzit, průmyslu a vlády: komparativní studie českých a slovenských zpracovatelských firem
Keywords: Propellants; University-Industry-Government; synergy; Comparative; study; Czech; and; Slovak; manufacturing; industries; Synergie; spolupráce; univerzit; průmyslu; vlády; komparativní; studie; českých; slovenských; zpracovatelských; firem